The Development of Social Attitude Assessment Instrument and Social Studies Learning Outcomes Grade IV on Theme of Indahnya Keragaman di Negeriku - Ikrima Maulida; I Ketut Dibia; I Gede Astawan (Universitas Pendidikan Ganesha, 2020)
The purpose of this study was to determine the quality of the results of the development of social attitude assessment instrument and social studies learning outcomes of grade IV on theme of Indahnya Keragaman di Negeriku. The development model used in this study is the 4D model. The 4D model consists of four stages: define, design, develop and disseminate. These four stages of the development model are used as a reference in producing and validating developed assessment instruments. The validation of the assessment instrument was carried out by two subject matter experts and 113 students for field trials. Data collected by questionnaire and test methods. The test instrument used was an objective test to assess student learning outcomes and the non-test instrument used was a questionnaire to assess students' social attitudes. The results of this study were the content validity test of 1.00 including the very high category, the item validity test produced 36 valid test items, the reliability test of 0.820 included very high criteria, the analysis of different power problems obtained 3 very good questions, 15 good enough questions, 11 questions good, and 7 questions are not good, the difficulty level analysis shows that there are 22 questions with easy criteria and 14 questions with moderate criteria.